Increasing the spectrum of white matter diseases with tigroid pattern on MRI: glutaric aciduria type 1 - case report - Monika Bekiesinska-Figatowska; Marek Duczkowski; Agnieszka Duczkowska; Joanna Taybert; Amanda Krzywdzinska; Jolanta Sykut-Cegielska (BMC, 2021)
Abstract Background Most white matter diseases present on magnetic resonance imaging as focal or diffuse T2-hyperintensities. However, in a few of them, radially oriented stripes of low (relatively normal) signal intensity are observed within diffusely affected T2-hyperintense cerebral white matter and are called "tigroid pattern" in the literature. The fornix is a tiny white matter fibers bundle playing crucial role in cognitive functioning, easily overlooked on magnetic resonance imaging and not described in inborn errors of metabolism. Case presentation We present a case of glutaric aciduria type 1 with a follow-up of over nine years. The course of the disease is presented in three magnetic resonance scans at the age of 8 and 21 months, and 10 years, with diffusion restriction in the fornix in scan 1 and 2 and with tigroid pattern in scan 3. Despite appropriate diet and supplementation, injury of white matter progressed achieving diffuse stage with tigroid pattern. Psychological tests revealed deficits in patient's specific cognitive skills, most likely related to damage to the fornix. Conclusions To our knowledge, this is the first report of tigroid pattern of white matter involvement in glutaric aciduria type 1 and the first report of forniceal injury in this disease which seems to be correlated with patient's low functioning in all kinds of memory skills, previously not reported in glutaric aciduria type 1.